Estatuas de sal: scheme for a tra(d) ición (tradition/betrayal) of women writers (Anclajes, 2024)
In the late eighties, the production of Cuban women writers began garnering visibility as a result of the work of academic groups, writers and artists. With or without institutional support, these groups organized and planned actions to promote gender consciousness and to establish the public presence of their history and cultural activities. A sign of this change is the 1996 publication of Estatuas de sal. Cuentistas cubanas contemporáneas by Mirta Yáñez and Marilyn Bobes, the first collection of fiction by Cuban women writers. This article analyzes the strategies for selecting and organizing the literary materials of Estatuas de sal. Although the editors of the book do not qualify it as an anthology but rather as “literary panorama”, we observe criteria that help to promote works and writers and introduce voices and textualities that struggle to penetrate mainstream Cuban culture. At the same time, the publication of this book highlighted a group of contemporary women writers and projects the future of narrative written by women.
Keywords: Cuban Literature; Female Writer; Anthology; Tradition; XX Century